2011
DOI: 10.1016/j.eururo.2011.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Features of Enhancing Renal Masses Predict Malignant and High-Grade Pathology: A Preoperative Nomogram Using the RENAL Nephrometry Score

Abstract: Background Counseling patients with enhancing renal mass currently occurs in the context of significant uncertainty regarding tumor pathology. Objective We evaluated whether radiographic features of renal masses could predict tumor pathology and developed a comprehensive nomogram to quantitate the likelihood of malignancy and high-grade pathology based on these features. Design, setting, and participants We retrospectively queried Fox Chase Cancer Center’s prospectively maintained database for consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
144
3
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(164 citation statements)
references
References 28 publications
10
144
3
7
Order By: Relevance
“…Higher nuclear grade and more unfavorable cancers have been shown to be related to the complexity of the renal tumors, according to their anatomic and topographic characteristics. 33 In the present study, positive margins were significantly greater in patients with Fuhrman 3/4 RCC compared with those with nuclear grade 1/2 (P < .0001). Furthermore, higher tumor grade was found to be an independent predictor of PSM at multivariate analysis (OR, 4.81; P ¼ .001; Table 4).…”
Section: Riccardo Schiavina Et Alsupporting
confidence: 49%
“…Higher nuclear grade and more unfavorable cancers have been shown to be related to the complexity of the renal tumors, according to their anatomic and topographic characteristics. 33 In the present study, positive margins were significantly greater in patients with Fuhrman 3/4 RCC compared with those with nuclear grade 1/2 (P < .0001). Furthermore, higher tumor grade was found to be an independent predictor of PSM at multivariate analysis (OR, 4.81; P ¼ .001; Table 4).…”
Section: Riccardo Schiavina Et Alsupporting
confidence: 49%
“…По данным литературы, сложность резекции почки по шкалам RENAL, PADUA и C-index коррелирует с риском развития осложнений и / или потенциаль-ной длительностью ишемии почки. Использование перечисленных выше шкал позволяет достаточно точно прогнозировать уровень риска предстоящей операции и выбрать правильную тактику лечения [20][21][22][23][24].…”
Section: Discussionunclassified
“…Nephrometry score is a proven metric of complexity that has utility for surgical planning and has been demonstrated to be predictive of outcomes following either PN or PCA 26,27 . In a study of 751 mixed renal tumors, Schmit and colleagues found that a R.E.N.A.L.…”
Section: Discussionmentioning
confidence: 99%